'It looks like a human!' The interrelation of social presence, interaction and agency ascription: a case study about the effects of an android robot on social agency ascription. Issue 4 (November 2016) - Straub, Ilona
Abstract This paper will focus on the establishment of a social event that refers in our case study to a social android robot simulating interaction with human users. Within an open-field study setting, we observed a shifting of interactive behavior, presence setting and agency ascription by the human users toward the robot, operating in parallel with the robots' different modulations of activity. The activity modes of the robot range from a simple idling state, to a reactive facetrack condition and finally an interactive teleoperated condition. By relating the three types of activity modes with three types of (increasing social) presence settings—ranging from co-location, to co-presence and finally to social presence—we observed modulations in the human users' interactive behavior as well as modulations of agency ascription toward the robot. The observations of the behavioral shift in the human users toward the robot lead us to the assumption that a fortification of agency ascription toward the robot goes hand in hand with the increase in its social activity modes as well as its display of social presence features.